The Relationship between Employment Status, Workload and Social Support on the Performance of Hospital Nurses - Dia Safitri; Muhammad Riza Setiawan; Nanik Marfu'ati; Susilo Budi Pratama (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Background: Nurse performance is a crucial indicator for determining the quality of healthcare services in hospitals. Poor nurse performance can increase the risk of adverse events and reduce patient and family satisfaction. Nurse performance is influenced by various indicators, including employment status, workload, and social support. Objective: This study aims to identify the correlation between employment status, workload, and social support with the performance of hospital nurses. Method: This study used an analytical observational design with a cross-sectional approach and purposive sampling technique. The study sample used were 84 nurses working at Dr. Adhyatma Regional General Hospital, MPH Semarang. The instrument in this study used a questionnaire. Data analysis used the chi-square test and the Spearman Rank test. Results: Indicates a substantial correlation between employment status and nurse performance (p = 0.024). And there is a substantial correlation between workload and nurse performance (p = 0.007) and there is a substantial correlation between social support and nurse performance (p = 0.005). Conclusion: There is a substantial correlation between employment status, workload, social support and nurse performance, the lighter the workload, the better the nurse's performance and high social support plays a role in improving nurse performance.